2003
DOI: 10.1177/0148607103027005355
|View full text |Cite
|
Sign up to set email alerts
|

Canadian clinical practice guidelines for nutrition support in mechanically ventilated, critically ill adult patients

Abstract: This guideline is a joint venture of the Canadian Critical Care Society, the Canadian Critical Trials Group, the Canadian Society for Clinical Nutrition, and Dietitians of Canada. The Canadian Critical Care Society and the Institute of Nutrition, Metabolism, and Diabetes of the Canadian Institutes of Health Research provided funding for development of this guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
919
6
91

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,341 publications
(1,038 citation statements)
references
References 54 publications
(93 reference statements)
22
919
6
91
Order By: Relevance
“…In the meta‐analysis, enteral nutrition within 24 h after ICU admission decreased mortality,288, 289, 290 the frequency of complication from infection,288, 289, 290 and length of hospital stay 291. However, the RCTs targeted by these meta‐analyses were small‐scale studies, and many were of low research quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the meta‐analysis, enteral nutrition within 24 h after ICU admission decreased mortality,288, 289, 290 the frequency of complication from infection,288, 289, 290 and length of hospital stay 291. However, the RCTs targeted by these meta‐analyses were small‐scale studies, and many were of low research quality.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Meta-analyses of the trials comparing nutritional support via the enteral and parenteral route in critically ill patients have been published, but interpretation of their results is complicated by small sample size, poor methodological quality, select groups of critically ill patients studied, lack of standardised definitions for outcome measures and interventions combining more than one element of nutritional support, for example timing and route.…”
Section: Background and Rationalementioning
confidence: 99%
“…3,4 Based on this evidence, use of IIT to achieve TGC has been advocated to improve outcomes for critically ill patients. 7,8 There have, however, been concerns regarding the broad application of IIT and TGC in critical illness. [9][10][11][12] Specifically, concerns have been raised about the methodology and overall generalizability of the two highest profile IIT trials reported by Van den Berghe et al 3,4 In particular, these trials were both single centre open-label trials where 87% of patients received parenteral nutrition.…”
Section: Commentarymentioning
confidence: 99%